PRODUCTION OF IMMOBILIZED LIPASE ITB1.2 AND ITS APPLICATION IN BIODIESEL SYNTHESIS USING WASTE COOKING OIL - Christopher Hasibuan, Abraham
Currently, the use of fossil fuels is increasing. On the other hand, fossil fuels such as petroleum and natural gas are increasingly difficult to obtain because they are depleting and have a negative impact on the environment. One application of the processed fossil fuels is diesel fuel for diesel engines. An alternative diesel fuel derived from renewable and environmentally friendly sources is biodiesel. Biodiesel production generally involves the transesterification of vegetable oil with alcohol using various types of catalysts, namely acid, base, and enzyme catalysts. This transesterification reaction requires vegetable oils and alcohols with low moisture content and low free fatty acid content to avoid the formation of by-products that can reduce the yield of fatty acid esters. Lipase catalysts offer an attractive alternative because they can avoid soap formation, produce high quality products, and are environmentally friendly. This research aims to synthesize immobilized lipase enzyme which is then applied for biodiesel synthesis from waste cooking oil. Immobilized lipase has advantages in terms of stability and can be used repeatedly. The preparation of immobilized lipase begins with the production of recombinant lipase ITB1.2 produced in Eschericia coli BL21 pITBlip1.2 with the obtained cell pellet of 0.5332 grams. The cell pellet was then lysed to produce enzyme crude extract (Ekstrak Kasar Enzim/EKE) which was further purified using Ni-NTA chromatography. Purified lipase ITB1.2 was obtained on elution using elution buffer containing 100 mM imidazole. The results of lysis and purification were characterized using SDS-PAGE electrophoresis. Furthermore, 16 mL of pure ITB1.2 lipase was concentrated using an Amicon Ultra-15 filter of 30 kDa size with a concentration of 20 times to produce 800 µL of concentrated enzyme. The activity test results showed that pure Lipase ITB1.2 had a hydrolysis activity of 29,595 U/mg and a transesterification activity of 0,547 U/mg. Furthermore, the enzyme immobilization process was carried out by IM-CLPCMC method and the immobilized lipase ITB1.2 enzyme was obtained much as 5.2 mg. The immobilized ITB 1.2 lipase was characterized by SEM and its transesterification activity was measured. Biodiesel synthesis was carried out using new and waste cooking oil substrates. The waste cooking oil was pre-treated using coconut fiber powder. The catalysts used in biodiesel synthesis were free and immobilized lipase ITB 1.2. The biodiesel obtained was further analyzed by TLC and GC-MS methods.